2009 Cotton Defoliation and Harvest Aid Guide - David L. Wright; Barry J. Brecke (EDIS)
Revised! SS-AGR-181, a 9-page illustrated guide by D. L. Wright and B. J. Brecke, discusses issues producers should consider concerning defoliation and harvest, and makes general recommendations for harvest-aid applications at various stages and conditions. Published by the UF Department of Agronomy, October 2009.